Social factors influencing behavioral intentions to vaccinate: personality traits and cues to action - Zeming Li; Xinying Sun (Frontiers in Psychology)
ObjectivesThis study integrates the Five-Factor Model (FFM) of personality traits with the Health Belief Model (HBM) to examine associations among personality traits, cues to action, and vaccination intentions.MethodAn online survey was conducted in April 2021, with 2,098 participants (mean age = 31.22 years, SD = 8.29) completing the study. The questionnaire assessed HBM constructs and the FFM personality traits. Spearman correlation coefficients were used to evaluate associations among ordinal variables, while Structural Equation Modeling (SEM) explored complex relationships between latent variables.ResultsThe findings indicate that self-efficacy (β = 0.198) and perceived barriers (β = 0.515) exert the most significant direct positive influences on vaccination intentions. Cues to action, particularly recommendations from family members (β = 0.113) and doctors (β = 0.092), also significantly affect vaccination intentions. Notably, personality traits indirectly influence vaccination intentions through self-efficacy and perceived barriers. Furthermore, agreeableness most significantly affects family suggestions, while neuroticism strongly influences recommendations from authority figures and healthcare providers, with extraversion notably impacting suggestions from peers.ConclusionsThe study highlights the influence of personality traits on cues to action, with neuroticism linked to authority influence, extraversion to peer influence, and agreeableness to familial influence. These findings emphasize the importance of incorporating individual differences into public health policies and vaccination promotion strategies. Future research should further explore the effects of diverse personality traits and community-specific profiles on vaccination behaviors to enhance intervention effectiveness.